Compound-specific short-chain carboxylic acids identified in a peat dissolved organic matter using high-resolution liquid chromatography–mass spectrometry. (September 2017) - Aristilde, Ludmilla; Guzman, Juan F.; Klein, Annaleise R.; Balkind, Reid J.
Highlights: Short-chain carboxylic acids were investigated in a peat dissolved natural OM (DNOM). Liquid chromatography coupled with high-resolution mass spectrometry was applied. Targeted compounds of biological origin were found in the peat DNOM isolate. Targeted m / z mass fragmentograms also captured unknown compounds. Five targeted carboxylic acids represented ppm fractions of total carboxyl content. Abstract: Dissolved natural organic matter (DNOM) is primarily composed of exuded or remnant biomolecules from plants and microorganisms. Labile amino acids and sugars have been well documented in the low molecular weight components of DNOM. However, little attention has been devoted to the isolation of labile short-chain carboxylic acids (SSCAs), which have demonstrated biogeochemical significance as sources of assimilable carbon, promoters of mineral dissolution, and ligands for metal complexation. Here we present an analytical method that identifies compound-specific SSCAs in a peat-derived DNOM isolate, Pahokee peat humic acid. Using high-resolution liquid chromatography (LC) coupled with high-accurate orbitrap mass spectrometry (MS), we targeted the identification of five SSCAs of different types: gluconate (a C6 monocarboxylic acid), citrate (a branched C6 tricarboxylic acid), 2-ketoglutarate (a C5 dicarboxylic acid), and malate and fumarate (C4 dicarboxylic acids). Following LC-separation and electrospray ionization, the compounds were annotated directly by orbitrap MS using their exact mass-over-charge ( m / z ) ions in the negative mode and their stoichiometric composition. Validated by LC–MS metabolite annotation in a bacterial matrix, we achieved identification of all five compounds in the peat DNOM isolate. Each targeted m / z channel also captured non-targeted compounds at different retention times, which represent isomers or different compounds. We found that the five targeted and the two non-targeted SSCAs identified collectively accounted for high parts-per-million to low parts-per-thousand of the total carbon, oxygen, or carboxyl content. Building on these findings, an important next step is to obtain a comprehensive profiling of SSCA structures in DNOM of different origins.